Dukungan Sosial Pengasuh Dalam Resiliensi Remaja Studi Kasus LKSA Muhammadiyah Sawangan - Kaisan, Ahmad Faris (Green Publisher Indonesia, 2025)
This study discusses how the form of social support carried out by caregivers on adolescent resilience at the Sawangan Depok Children's Social Welfare Institution. Social support can help a person cope with stress, improve their mental and physical health, and achieve their life goals if they receive help and resources from others in their social network. In this case, the study was conducted to find out the form of social support provided by caregivers, as well as its impact on adolescent resilience at the Children's Social Welfare Institute (LKSA) Muhammadiyah Sawangan Depok. The approach used by the researcher in this study is through a qualitative case study approach, where in the data collection technique the author conducts observations, interviews, and documentation studies. The informants in this study were seven people consisting of a caregiver and six teenagers living in LKSA. The results of the study showed that LKSA caregivers have fulfilled instrumental support in adolescents, where this aspect is more dominant than reward support and informational support. However, caregivers need to pay more attention to emotional support. Then the impact on adolescent resilience can be seen from the dominant I Am which has an impact on adolescents where this aspect can affect the increase of resilience ability in the I Have and I Can aspects of resilience.